Urgensi Etika Komunikasi dalam Meminimalisir Perundungan Siber Melalui Akun Anonim Pada Media Detik Forum (Studi Kasus pada Influencer Rachel Vennya Roland) - Cahya Khairani; Trisnina Luthfi Aisyah; Hasan Sentosa Lukito; Hasan Sazali; Maulana Andinata Dalimunthe (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
The presence of the internet and social networking platforms has both positive and negative impacts depending on how you use them. The positive impact will bring and develop knowledge and be able to share information with each other while the negative impact will lead to actions that will unwittingly take victims due to the irresponsibility of the perpetrator. One of the negative consequences of using the internet and digital communication methods is cyberbullying. This study used qualitative research methods. The use of qualitative research in this study is because the formulation of the problem in this study requires the use of a qualitative model, because when formulating the existing problem, the researcher wants to understand how the content of the comments contained in the detikForum discussion forum. There are various types of cyberbullying carried out by detikForum users. Generally in the form of cyber bullying, flaming and denigration. Stop cyberbullying by understanding communication ethics again so that you can filter the posts that will be sent on social media so that the writing does not hurt other people.